2010
DOI: 10.1177/1356766709356139
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between Thai residents and non-residents in their motivations, performance evaluations, and overall satisfaction with a domestic festival

Abstract: Competitiveness among destinations, the rising cost of marketing, and the need to maintain market share, inspire the event management of the Tenth-Month Merit-Making Festival (TMMF) to use the festival as a tourist destination and to focus on attendees' wants and needs. The TMMF is a religious celebration which has existed in Nakhon Si Thammarat (NT), a province in southern Thailand for more than a hundred years. Despite the longevity and significance of the TMMF, there is no systematic record of the festival'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 27 publications
5
20
1
3
Order By: Relevance
“…Accordingly, previous studies on festivals and special events have been interested in examining the relationships between festival audience members' motivations, quality of the performance and the experience, audience satisfaction levels, and future behavioral intentions (Cole & Illum, 2006;Kim, 2008;Kim et al, 2008;Lee et al, 2004;McDowall, 2010). In a case study of the 2000 Kyongju World Expo, Lee et al (2004) confirmed that there was a direct relationship between festival motivations and satisfaction.…”
Section: Festival Audience Motivation Satisfaction and Intention Tosupporting
confidence: 63%
See 2 more Smart Citations
“…Accordingly, previous studies on festivals and special events have been interested in examining the relationships between festival audience members' motivations, quality of the performance and the experience, audience satisfaction levels, and future behavioral intentions (Cole & Illum, 2006;Kim, 2008;Kim et al, 2008;Lee et al, 2004;McDowall, 2010). In a case study of the 2000 Kyongju World Expo, Lee et al (2004) confirmed that there was a direct relationship between festival motivations and satisfaction.…”
Section: Festival Audience Motivation Satisfaction and Intention Tosupporting
confidence: 63%
“…Given that the sustainability of festivals depends greatly on the level of satisfaction of festival audience members at the event (Crompton & McKay, 1997), understanding of the festival audience members and their motivations; a festival's performance evaluation; and the festival's overall satisfaction for the audience member, are all key factors for the staging of a successful festival (McDowall, 2010). Accordingly, previous studies on festivals and special events have been interested in examining the relationships between festival audience members' motivations, quality of the performance and the experience, audience satisfaction levels, and future behavioral intentions (Cole & Illum, 2006;Kim, 2008;Kim et al, 2008;Lee et al, 2004;McDowall, 2010).…”
Section: Festival Audience Motivation Satisfaction and Intention Tomentioning
confidence: 99%
See 1 more Smart Citation
“…By addressing a topic of contemporary interest, such as the underlying forces of festival visitors' behavior, in thus far scarcely examined context of cultural events in Slovakia, findings of this study add to The application of factor analysis indicated six domains of visitors' motivation, such as new and different experience, friends and family togetherness, reconnection with culture and tradition, socialization, equilibrium recovery and change from everyday. Findings of this study which indicate a multidimensional nature of event attendees' motivation and the before mentioned domains of motivation as the main drivers of visitors' decision to attend a traditional cultural event, are largely in compliance with previous research (Mohr et al, 1993;Lee et al, 2004;McDowall, 2010;Park et al, 2014). Taking into consideration the domains of motivation which emerged from previous research and the ordering of the dimensions of attendees' motivation stemming from this study, from the perspective of explained variance in visitors' motivation, results of this study are in accordance with Nicholson and Pearce's (2001) findings that visitors' behavior is directed by largely similar internal factors, however, motivational domains differ in terms of their importance across various event settings.…”
Section: Discussionsupporting
confidence: 60%
“…Cudny and Ogorek (2014) conducted a study addressing visitors' motivation in the setting of Mediaschool Film Festival held in Lodz, Poland, and their research indicated six motivational domains, whereas the most important domain was related to culture and art, followed by social contacts, originality / novelty, event attractiveness, escape from everyday routine and family life. Previous studies have indicated differences in importance of motivation domains based on festival setting, previous visitation, visitors' residential status and national culture (Mohr et al, 1993, Lee et al, 2004, McDowall, 2010, Park et al, 2014. On the basis of previous discussion the following hypotheses are proposed: H1: Visitors' motivation to attend traditional cultural festivals in Slovakia is a multi-dimensional construct;…”
Section: Literature Reviewmentioning
confidence: 99%